Improving the Ability to Writing Short Stories Through the Development of Teaching Materials for Students of Grade IX of Budhi Mulia Integrated Junior High School - Firdaus, Riksa Fathan; Ristiani, Iis (The Eastasouth Journal of Social Science and Humanities, 2025)
This study aims to improve the short story writing skills of grade IX students of Budhi Mulia Integrated Junior High School through the development of contextual teaching materials that are in accordance with the characteristics of students. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the feasibility test of teaching materials indicate that the developed module is feasible to use, based on validation by material experts, media experts, and responses from teachers and students. After implementation, there was a significant increase in short story writing skills, seen from the increase in students' writing scores in the final assessment. This shows that the teaching materials developed are effective in helping students develop ideas, plots, characters, and messages in short stories. This study recommends the development of similar teaching materials with a thematic approach and based on personal experience for literature learning at the junior high school level.